Issues in financial sector reforms - Tarapare,S S (New Delhi UBSPD, 2000)
The present volume focusses on banking sector reforms as well as the problems of non-banking financial institutions and also deals in the integrated manner with issues relating to monetary, fiscal and external sectors. There is an exhaustive treatment of
Keywords: Finance-India; Monetary policy-India; Banks and banking-India